Study of pregnancy outcome of threatened abortion and its correlation with risk factors in a tertiary care hospital of Mumbai, India - Sivasane, Dipali S.; Daver, Rekha G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Early pregnancy loss is very common and, in most cases, it can be considered as nature’s method to select for a genetically normal offspring. Threatened abortion is a relatively common complication during pregnancy, occurring in approximately 20% of all pregnancies. Maternal age, Outcome of previous pregnancies, health of mother, any infection etc can be decisive factors in the risk of pregnancy loss. Methods: The present study was a cross sectional study where patients admitted with threatened abortion were interviewed using pretested semi-structured questionnaire after the treatment. Outcome of pregnancy was recorded. Their basic socio-demographic data along with possible risk factors were recorded. TORCH Ig M and Ig G were done in all patients. Results: Out of 95 patients admitted with threatened abortion, 42 (44%) patients undergone abortion whereas in 53 (56%) patients, pregnancy was continued. Out of total 60 patients admitted with the complain of only vaginal spotting, in 39 pregnancy continued and in 21 patients pregnancy was aborted. (p-value<0.05). 50.52% were from age group of 21 to 25 years of age. It was also seen that after 35 years of age, significant number of patients aborted. Out of these 11 patients with high BMI, pregnancy was continued only one patient. Out of total 20 patients positive for IgM of toxoplasma infection, pregnancy was aborted in 13 (65%) patients. Out of total 15 patients positive for IgM of cytomegalo virus infection, pregnancy was continued in 11 (73.3%) patients. Conclusions: Patients of threatened abortion with only symptom of spotting per vagina have good chances of continuation of the pregnancy. Increased maternal age above 35, Overweight and bad obstetric history are also associated with pregnancy loss. Though there was no statistically significant difference it was evident that among all TORCH infections, IgM toxoplasma and Rubella are associated more with pregnancy loss.